“A Hollow Sham”: The Representation of War in Bernard Shaw’s Victorian Plays - Stéphane Guy (Cahiers Victoriens et Edouardiens)
A fierce opponent to war prompted by passion, Bernard Shaw saw the contemporary stage as the source of the Victorians’ misconception of the battlefield. In his plays, comedy and derision debunk the warped view of fighting that flows from ideals, the thirst for revenge and an incompetent ruling class. The onslaught goes hand in hand with the staging of an alternative form of heroism for the audience that defeats their aesthetic expectations through dramatic paradox. Shaw’s war plays unfold a dramaturgy of verisimilitude aiming to break down artifice and playing with the very principle of representation of conflict on the stage.